Tourism and hospitality : perspectives, opportunities and challenges - Krebs, Rafael A. (New York : Nova Science Publishers, Incorporated, 2018)
In this compilation, the authors investigate factors that stop female participation in leisure cycling using research combining literature on LTPA gender constraints, cycle tourism and cycling in general to contribute to the little existing knowledge of female cycling constraints. The westernized way of understanding culture, marked by Eurocentric defensive self-tropings and policies of world colonization, is addressed and contrasted with that of non-western communities. An essay-review is presented focusing on the role of alcohol consumption within the rite of hospitality, defining hospitality as, an ancient inter-tribal pact, which ensures the common defence in case of wars and person-exchanges for peace-times. Later, six dimensions of the value of the information obtained in social media by Generation Y travelers were identified in these context of research: the utilitarian value, the risk avoidance, the hedonic value, the sensations felt during the process of search, the value of the interaction with other users, and the perceived congruence between the information obtained in these virtual sources and the identity of the consumer. The authors go on to examine to what extent the adoption of robots to meet with guests and their needs prompts what some scholars deem the death or the end of hospitality. While some scholars lament the introduction of robots, others understand the trends in leisure and consumption are changing daily. Derridas views on hospitality in relation to unwanted pregnancy are studied, including his views on invitation and visitation. Following this, the authors examine the problem of fragmentation experienced by tourism-applied research in recent years. The socio-economic factors that prevented tourism its maturated and stylized form are discussed. In closing, the critical limitations and problems of tourism research today are explored.
Preface -- Chapter 1. Alcohol Consumption and Hospitality: Surfing Through Uncertainty -- Chapter 2. The Dimensions of the Perceived Value of the Information Obtained by Generation Y Tourists in Social Media -- Chapter 3. Awakening: A Critical Discussion of the Role of Robots in the Rite of Hospitality -- Chapter 4. The Anthropology of Tourism: Discussing New Paths and Perspectives -- Chapter 5. Failed Prestige: Problems and Quandaries of Tourism Discipline over 40 Years.
Includes bibliographical references and index.
Keywords: TOURISM